Body image satisfaction and self esteem among undergraduate female nursing students in School of Health Sciences Universiti Sains Malaysia - Mumim, Juliana Simbah Anak (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2021)
The effect of body image on self-esteem is very important in the life phase of students and adolescents. This study is done to determine the level of body image satisfaction and selfesteem among undergraduate female nursing students in School of Health Sciences, Universiti Sains Malaysia (USM). A cross-sectional study involving 152 respondents via convenient sampling. A questionnaire survey was used for data collection from October 2020 to July 2021. The test that used in this study was descriptive statistics and Simple Logistic Regression using Statistical Package of Social Sciences (SPSS) version 26.0. The findings revealed that 80.9% respondents had a positive body image while 19.1% respondents had a negative body image. Besides that, 84.2% respondents had high self-esteem while 15.8% respondents had low self-esteem. There was no association between body image satisfaction and self-esteem as p = 0.07 (P <0.05), but it was found that respondents with positive body image satisfaction were 0.16 times had high self-esteem. In conclusion, new education and awareness strategies for promoting positive body image attitudes are needed.